3x - (2x + 8) = -6
3x -2x - 8 = -6
x - 8 = -6
x - 8 + 8 = -6 + 8
x = 2
From the recursive rule, you can tell the initial value is 3 and the common ratio is 12. The explicit rule is always
.. (n-th term) = (initial value)*(common ratio)^(n -1)
Subsituting the values you know, you have
.. an = 3*12^(n-1)
Answer:
see explanation
Step-by-step explanation:
let ∠BCE = x then ∠ECD = 5x - 6 and
∠BCE + ∠ECD = ∠BCD, substitute values
x + 5x - 6 = 162, that is
6x - 6 = 162 ( add 6 to both sides )
6x = 168 ( divide both sides by 6 )
x = 28
Hence
∠BCE = x = 28°
∠ECD = 5x - 6 = (5 × 28) - 6 = 140 - 6 = 134°
<em>Look</em><em> </em><em>at</em><em> </em><em>the</em><em> </em><em>attached</em><em> </em><em>picture</em><em> </em><em>⤴</em>
<em>Hope</em><em> </em><em>it</em><em> </em><em>will</em><em> </em><em>help</em><em> </em><em>u</em><em>.</em><em>.</em><em>.</em>
<em>✴</em><em>Have</em><em> </em><em>a</em><em> </em><em>great</em><em> </em><em>day</em><em>✴</em><em>✴</em>